The antidepressant-like effects of an n-butanol fraction of Ocimum sanctum Linn. extract in unpredictable chronic mild stress-induced depression in mice - Thu Hien Nguyen; Thi Xoan Le; Van Tai Nguyen; Thi Nguyet Hang Pham; Minh Khoi Nguyen; Matsumoto Kinzo (Vietnam Journal of Science, Technology and Engineering, 2021)
We previously reported that Ocimum sanctum Linn. (OS) ethanolic extract and its n-butanol fraction (OSB) could improve depression-like behaviour in olfactory bulbectomized mice. The present study aims to clarify the antidepressant-like effects of OS-B and the possible mechanism of its action using mice subjected to unpredictable chronic mild stress (UCMS). UCMS mice were administered daily with OS-B (50 mg/kg, 100 mg/kg, p.o.) or imipramine (IMP, 8 mg/kg, i.p.), a reference drug. The UCMS-induced anhedonia in mice was analysed by the sucrose preference test, while behavioural despair was assessed using the tail suspension test (TST) and forced swimming test (FST). Locomotor activities and grooming behaviour of mice were elucidated using the open-field test (OFT). The UCMS procedure for 5 weeks induced anhedonia, and this symptom was significantly ameliorated by the administration of OS-B (100 mg/kg) as well as IMP during the UCMS period. Moreover, the OS-B and IMP treatment attenuated the UCMS-induced enhancement of behavioural despair in the TST and FST. In OFT, mice subjected to UCMS showed a decrease in grooming behaviour, and the effect of UCMS was reversed by OS-B and IMP administrations. No significant difference in locomotor activities between each animal group was observed. The amelioration effects of OS-B and IMP on UCMS-induced behavioural despair in the TST were abolished by administrating of ρ-chlorophenylalanine (PCPA, 80 mg/kg, i.p), a tryptophan hydroxylase inhibitor, and α-methyl-ρ-tyrosine (AMPT, 100 mg/kg), a tyrosine hydroxylase inhibitor. The present results suggest that OS-B attenuates UCMS-induced depression-like symptoms via monoaminergic systems including in the noradrenergic, dopaminergic, and serotonergic system.